Histamine Content in Dried Fish Products from Kakinada Coast - R., Chakrabarti (Fishery Technology, 2025)
The content of histamine, total volatile base nitrogen and salt were determined in 31 varieties of dried samples collected from Kakinada. Most of the gutted, salted and dried fish samples contained histamine below 10mg/100g of musele, Histamine content in ungutted salted and dried fish was more than that in gutted, salted and dried fish. In whole dried mackerel it was 80.614822 mg%. During summer,histamine level in whole sun dried white bait reached above 100mg/l 00g in a few cases while in winter histamine level was almost half. TVBN values did not show any correlation with the histamine content of fish samples.